2020
DOI: 10.5539/jas.v12n11p56
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ Preferences for Varietal Traits, Their Knowledge and Perceptions in Traditional Management of Drought Constraints in Rice Cropping in Benin: Implications for Rice Breeding

Abstract: Rice (Oryza spp.) is one of the most important crops that significantly contribute to food security in Benin. In the current context of climate change, drought is known to be the main abiotic stress in crops and a major yield-limiting factor for agricultural production worldwide. To assess farmers’ knowledge, the preference traits of the rice cultivars in use, their perceptions and management of drought stress in rice production in Benin, an ethnobotanical investigation was conducted in 50 villages t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 38 publications
1
3
0
2
Order By: Relevance
“…It can equally help to bridge the demand-supply deficit for rice in Nigeria, all things being equal. This is in line with the findings of Fatondji, et. al.…”
Section: Major Rice Varieties Grown By the Farmerssupporting
confidence: 93%
See 1 more Smart Citation
“…It can equally help to bridge the demand-supply deficit for rice in Nigeria, all things being equal. This is in line with the findings of Fatondji, et. al.…”
Section: Major Rice Varieties Grown By the Farmerssupporting
confidence: 93%
“…(2020) also assert that factors such as potential yield, early maturity, pest-disease resistance, cooking quality, etc influence the preference for rice variety among rice farmers. Similarly, Fatondji et al (2020) revealed that farmers' preferences for rice variety are basically on certain plant features such as high grain yield. According to Rahman and Connor (2022), farmers who adopt rice varieties of high-yielding qualities like FARO 44 have high income and better nutrition.…”
Section: Major Rice Varieties Grown By the Farmersmentioning
confidence: 99%
“…Teknik ini mampu menghasilkan benih bermutu sebagai faktor penting untuk meningkatkan produktivitas komoditas pertanian. Petani juga dapat berperan dalam pendaftaran varietas, pemeliharaan tanaman, distribusi produk, dan komersialisasi produk hilir bersama pemulia (Fatondji et al 2020).…”
Section: Sistem Perbenihan Nasionalunclassified
“…Proses pemuliaan partisipatif idealnya mencakup peserta yang terdiri atas kelompok petani (laki-laki dan perempuan), anggota lembaga akademik, penyuluh, pejabat pemerintah, penjual, dan unsur lain yang terlibat aktif dalam pertanian. Penilaian yang berasal dari stake holder tersebut digunakan dalam analisis gender dan membandingkan keterlibatan peserta pria dan wanita (Fatondji et al 2020).…”
Section: Komponen Pemuliaan Padi Partispatifunclassified
“…Participatory breeding was developed using indigenous knowledge to accelerate the adoption of new varieties. Decentralization provides farmers with the opportunity to influence varieties according to their specific agro-ecological needs and to improve the breeding programs [12,13]. Importance Performance Analysis is also used to complement farmers' responses to the rice lines.…”
Section: Introductionmentioning
confidence: 99%